Ternary positive electrode material having high safety and method for producing the same

By enhancing the ratio of Mn and Co elements on the surface of high nickel single crystal positive electrode material, a Li-Co-Mn-O layered structure is formed, which solves the problem of insufficient oxygen release and thermal stability at high temperatures, and improves the high thermal stability and dynamic performance of high nickel ternary positive electrode material.

JP7660160B2Active Publication Date: 2025-04-10SHANGHAI RUIPU ENERGY CO LTD
View PDF 20 Cites 0 Cited by

Patent Information

Application Number
JP2023083285
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-05-19
Filing Date
2023-05-19
Publication Date
2025-04-10
Estimated Expiration
2043-05-19

AI Technical Summary

Technical Problem

The existing high-nickel ternary cathode materials lack oxygen release and thermal stability at high temperatures, which affects battery safety and performance.

Method used

High nickel single crystal positive electrode material is used to enhance the ratio of Mn and Co elements through the surface to form a Li-Co-Mn-O layered structure, improving the thermal stability and dynamic performance of the material.

Benefits of technology

It significantly improves the thermal stability and cyclic stability of high-nickel ternary cathode materials, reduces gas generation and capacity reduction at high temperatures, and improves the safety and performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007660160000004
    Figure 0007660160000004
  • Figure 0007660160000001
    Figure 0007660160000001
  • Figure 0007660160000002
    Figure 0007660160000002
Patent Text Reader

Abstract

To provide a ternary positive electrode material having high safety, and a production method thereof.SOLUTION: A ternary positive electrode material having high safety, and a production method thereof are disclosed according to the present invention. The ternary positive electrode material has a chemical composition given by Lia(NixCoyMn1-x-y)1-bMbO2-cAc, where 0.75≤a≤1.2, 0.75≤x<1, 0<y≤0.15, 1-x-y>0, 0≤b≤0.01 and 0≤c≤0.2, M is one or more kinds selected from a group consisting of Al, Zr, Ti, Y, Sr, W and Mg, A is one or more kinds selected from a group consisting of S, F and N, and CMn-(1-x-y)≥0.07, CCo-y≥0.05, and 0≤[CMn-(1-x-y)] / (CCo-y)≤2.0. The ternary positive electrode material of the invention is a high-nickel single crystal material having a concentration gradient. The ternary positive electrode material has advantages, such as a high capacity and high heat stability and it is easy to fabricate, and suitable for large scale production.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention belongs to the technical field of batteries, and relates to a battery positive electrode material, and more particularly to a highly safe ternary positive electrode material and a method for producing the same. [Background technology]

[0002] Ternary cathode materials with the α-NaFeO2 structure have high capacity per gram and excellent rate characteristics, and therefore can be applied as cathode materials for power batteries in fields such as high-performance electric vehicles and energy storage.

[0003] In the ternary cathode material, Ni element changes its valence during the charge / discharge process and is the main contributor to capacity and energy. Co element contributes to increasing the rate capability and structural stability of the material. Mn / Al elements increase the oxygen release temperature of the material and increase the thermal stability of the cathode material.

[0004] In order to obtain higher battery energy density, it is possible to increase the Ni content in the ternary material. However, this method reduces the ratio of Co / Mn elements in the material. The decrease in tetravalent Mn in the transition metal layer leads to the decrease in divalent Ni, so the ratio of trivalent ions in Ni element increases to maintain the charge balance in the crystal structure. This directly affects the stability of the material. When the material is in a high lithium depletion state, oxygen release is likely to occur, which affects the safety of battery use.

[0005] The construction of a cathode material with a concentration gradient can solve the balance problem between the capacity per gram of the material and the thermal stability. The literature Nat Commun 12, 2350 (2021) presents a method for coating the surface of a high-nickel material with a medium-low nickel coating layer, and succeeded in obtaining a high-nickel polycrystalline material that has both high capacity and stability. However, this method is not suitable for large-scale production because precise control is already required at the precursor stage of material synthesis. In addition, this method is only suitable for the preparation of polycrystalline ternary cathode materials, and not for single-crystalline materials. This is because precursors with a concentration gradient may lose their concentration difference due to solid-phase diffusion of metal ions during the high-temperature sintering process. [Prior art documents] [Non-patent literature]

[0006] [Non-Patent Document 1] Nature Communications, 12, 2350(2021) Summary of the Invention [Problem to be solved by the invention]

[0007] In order to solve the above problems, the object of the present invention is to provide a ternary cathode material with high safety and a method for preparing the same. This material is a high nickel single crystal material with a concentration gradient, which has the advantages of high capacity and high thermal stability, and the method is simple and suitable for large-scale production. [Means for solving the problem]

[0008] The object of the present invention is achieved by the following technical solutions.

[0009] <First aspect> The present invention is a compound having a chemical composition of Li a (Ni x Co y Mn 1-x-y ) 1-b M b O 2-c A c and 0.75≦a≦1.2, 0.75≦x<1, 0<y≦0.15、1-x-y> 0, 0≦b≦0.01, 0≦c≦0.2; M is selected from one or more of Al, Zr, Ti, Y, Sr, W, and Mg; A is a ternary positive electrode material for a lithium ion battery selected from one or more of S, F, and N; The ternary cathode material has a single crystal morphology, and C Mn -(1-xy)≧0.07, and C Mn is the atomic ratio of Mn element to the total of Ni, Co, and Mn elements obtained by surface measurement of the material using XPS, C Co -y≧0.05, C Co is the atomic ratio of Co to the total of Ni, Co, and Mn elements obtained by surface measurement of the material using XPS, 0≦[C Mn -(1-xy)] / (C Co -y)≦2.0; We provide ternary positive electrode materials for lithium-ion batteries.

[0010] In the present invention, C Mn -(1-xy)≧0.07; C Mn is the atomic ratio of Mn element obtained by XPS surface measurement of the material to the total of Ni, Co, and Mn elements obtained by XPS surface measurement of the material, C Co - y ≧ 0.05; C Co is the atomic ratio of Co element obtained by surface measurement using XPS to the total of three elements Ni, Co, and Mn obtained by surface measurement using XPS.

[0011] In one or more embodiments, C Mn -(1-xy)≦0.40 is sufficient.

[0012] In one or more embodiments, C Co -y≦0.35 is sufficient.

[0013] In one or more embodiments, C Mn -(1-xy)≧0.15 is sufficient.

[0014] In one or more embodiments, C Co -y≧0.1 is fine.

[0015] In a typical high-nickel ternary cathode material, the ratio of Ni, Co, and Mn elements on the surface is the same as that in the bulk phase, with a high Ni content. During the charge and discharge process of a lithium-ion battery, the valence changes, and especially when the battery is fully charged, the Ni 2+ / Ni 3+ However, the more expensive Ni 4+ This converts to cations, which are prone to side reactions with the solvent and additives in the electrolyte, resulting in adverse effects such as deterioration of battery performance and gas generation.

[0016] In the present invention, the content of Mn element in the surface of the high-nickel positive electrode material is relatively increased by ≥ 7% and the content of Co element is increased by ≥ 5% as the ratio of the three main metal elements compared to the whole, thereby reducing the content of Ni element at the material surface by ≥ 12%. This not only maintains the high capacity per gram and excellent rate characteristics of the high-nickel material, but also significantly reduces the amount of gas generation under high-temperature storage conditions and the capacity loss during high-temperature cycles. Furthermore, by increasing the ratios of Mn element and Co element at the surface to ≥ 15% and ≥ 10%, respectively, compared to the whole, a high-nickel ternary positive electrode material with even better dynamic performance and thermal stability can be obtained.

[0017] In one or more embodiments, the particle size D at which the particle volume cumulative distribution of the ternary positive electrode material reaches 50% v50 2.5μm≦D v50The particle size of the material is less than 5 μm. If the particle size of the material is smaller than this range, the overall particle size is too small, and the material has problems such as low compaction and too large active surface area, making it difficult to obtain a lithium-ion battery with high energy density. On the other hand, if the particle size of the material is larger than this range, the solid-phase diffusion distance of lithium ions will increase due to the excessively large particle size, leading to deterioration of rate characteristics.

[0018] <Second aspect> The present invention provides a method for preparing a ternary cathode material for a lithium-ion battery, comprising the steps of: S1: Select a ternary positive electrode precursor containing Ni, Co, and Mn, and mix it with lithium hydroxide to form mixture A; S2: Heat mixture A in an air or oxygen gas atmosphere, hold it at 700°C to 1100°C for 4 to 15 hours, and obtain intermediate product B through roller and crushing. If the sintering temperature in this process is lower than 700°C, it is difficult to completely convert the precursor into a ternary positive electrode material having a layered structure. On the other hand, if the sintering temperature is higher than 1100°C, the Ni in the transition metal layer in the high nickel material will be formed. 2+ Li in the lithium ion layer + and exchange in large quantities, causing severe mixing in the material and reducing the capacity per gram of material; S3: Mix intermediate product B with a Mn-containing solid powder and a Co-containing solid powder to form a mixture C, in which the ratio of the amount of substance of Mn element in the Mn-containing solid powder to the amount of substance of intermediate product B is 0.5% to 4%, and the ratio of the amount of substance of Co element in the Co-containing solid powder to the amount of substance of intermediate product B is 2% to 4%; S4: Mixture C is heated in an air or oxygen gas atmosphere, and is maintained at 700°C to 1100°C for 4 to 15 hours, and then the ternary positive electrode material for lithium ion batteries is obtained through rolling and pulverization.

[0019] In one or more embodiments, in step S1, the ternary positive electrode precursor containing Ni, Co, and Mn is a ternary hydroxide precursor.

[0020] In one or more embodiments, in step S1, a ternary positive electrode precursor containing Ni, Co, and Mn is prepared as follows: an aqueous solution is prepared from three metal salts, namely nickel sulfate, manganese sulfate, and cobalt sulfate, according to a predetermined ratio, so that the total concentration of the metal salts is 1.5 mol / L to 4 mol / L; a mixed aqueous solution of sodium hydroxide and ammonia water is added thereto as a precipitant, so that the NaOH concentration in the mixed aqueous solution is 3 mol / L to 4.5 mol / L, and NH4OH is 0.01 to 0.1 mol / L. The concentration is 2 mol / L to 3.5 mol / L, the molar ratio of NaOH to the sum of the three metal salts is 2:1 to 2.5:1, and the molar ratio of NH4OH to the sum of the three metal salts is 1:1 to 2:1; react under a protective atmosphere (e.g., nitrogen gas), maintain the reaction temperature at 45°C to 60°C, the pH value of the reaction is 10 to 12, and the stirring speed is 900 r / min to 1200 r / min; wash after 9h to 15h of reaction, and vacuum dry at 75°C to 90°C for 10h to 30h to obtain a ternary hydroxide precursor.

[0021] In one or more embodiments, in step S1, the preparation of a ternary positive electrode precursor containing Ni, Co, Mn is as follows: prepare a 2 mol / L solution from three metal salts consisting of nickel sulfate, manganese sulfate, and cobalt sulfate according to a predetermined ratio; add a mixed solution of sodium hydroxide (concentration 4 mol / L, the molar ratio of NaOH to the sum of the three metal salts is 2:1) and ammonia water (concentration 2.4 mol / L, the molar ratio of NH4OH to the sum of the three metal salts is 1.2:1) as a precipitant, react under a protective atmosphere (nitrogen gas), maintain the reaction temperature at 55°C±1°C, make the pH value of the reaction 11.0, and stir speed 1000r / min; wash after 12h of reaction, and vacuum dry at 80°C for 24h to obtain a ternary hydroxide precursor.

[0022] In one or more embodiments, in step S2, mixture A is heated in an oxygen gas atmosphere.

[0023] In one or more embodiments, in step S1, an oxide of element M may or may not be added as a dopant.

[0024] In one or more embodiments, an oxide of element M may or may not be added as a coating agent in step S3.

[0025] In one or more embodiments, in step S1, a compound containing element A as a dopant may or may not be added.

[0026] In one or more embodiments, a compound containing element A may or may not be added as a coating agent in step S3.

[0027] In one or more embodiments, in step S1, an oxide of element A may or may not be added as a dopant.

[0028] In one or more embodiments, an oxide of element A may or may not be added as a coating agent in step S3.

[0029] In one or more embodiments, in step S3, the Mn-containing solid powder is one or more of MnO2, Mn2O3, MnO(OH), and MnO. The use of these Mn-containing solid powders facilitates the formation of a Li-Co-Mn-O compound having a layered structure on the surface of the single crystal material.

[0030] In one or more embodiments, the Co-containing solid powder is one or more of Co3O4, CoO, Co(OH)2, CoOOH, and CoCO3. The use of these Mn-containing solid powders facilitates the formation of a Li-Co-Mn-O compound having a layered structure on the surface of the single crystal material.

[0031] In one or more embodiments, in step S3, the ratio of the amounts of Mn and Co in the Mn-containing solid powder and the Co-containing solid powder is 1:4 to 1:1.

[0032] <Third aspect> A positive electrode sheet for a lithium ion battery using the above-mentioned ternary positive electrode material or using the ternary positive electrode material produced by the above-mentioned method is included in the scope of protection of the present invention.

[0033] A positive electrode sheet for a lithium ion battery containing the above-mentioned ternary positive electrode material or containing the ternary positive electrode material produced by the above-mentioned method is included in the scope of protection of the present invention.

[0034] <Fourth aspect> A lithium ion battery using the above positive electrode sheet is also included in the scope of protection of the present invention.

[0035] A lithium ion battery including the positive electrode sheet is also included in the scope of protection of the present invention.

[0036] Compared with the conventional technology, the present invention has the following advantages:

[0037] 1) In the ternary cathode material of the present invention, the Ni content of the main elements (Ni, Co, Mn) is higher than 75%, and it has a high capacity per gram (materials with a Ni content higher than 75% have relatively poor stability and need to be surface treated by the method of the present invention). At the same time, the material has a single crystal morphology, there is little aggregation of multiple crystal grains, and the possibility of lattice defects occurring during the charge and discharge process is significantly reduced compared to polycrystalline materials, and it has excellent cycle stability.

[0038] 2) In the ternary cathode material of the present invention, the ratio of Mn element on the surface is 0.07 or more higher than the total, so that the stability of the material at high temperatures is improved. The increase in the ratio of tetravalent Mn ions increases the potential at which the H2-H3 transformation occurs in the material, so that irreversible changes in the material during the charge and discharge process are reduced. When the cathode is subjected to heat, the electrolyte may react with the active oxygen released from the cathode, causing thermal runaway, and this process begins on the surface of the cathode material. Therefore, such a material design significantly improves the resistance of the battery to thermal runaway.

[0039] 3) In the ternary cathode material of the present invention, the ratio of Co element on the surface is 0.05 or more higher than the total, so that the rate characteristics of the material are improved. The cobalt-containing oxide / hydroxide can react with the residual lithium salt on the surface of the material to form a composite lithium metal oxide, which reduces the amount of free lithium on the surface of the material and reduces the gas generation of the material at high temperatures.

[0040] 4) In the ternary cathode material of the present invention, both Mn and Co compounds cover the high nickel cathode material, making it possible to produce a single crystal material with a high Co / Mn surface and high Ni inside. A coating with only Co improves the rate characteristics of the material and reduces the amount of lithium compounds remaining on the surface, but does not improve the stability of the material. On the other hand, a coating with only Mn does not build a layered structure on the surface of the material, which may react with free lithium and form lithium manganate, resulting in lattice mismatch with the main body of the material and reducing the capacity per gram and rate characteristics of the material. A coating is performed using Co and Mn simultaneously, and the ratio of both in the coating layer is [C Mn -(1-xy)] / (C Co By satisfying the condition (-y)≦2.0, it is possible to construct a surface structure of a positive electrode material that simultaneously has excellent rate characteristics and stability.

[0041] 5) In the ternary positive electrode material of the present invention, the particle size range when the cumulative volume distribution reaches 50% is preferably 2.5 μm to 5 μm. At this time, the active specific surface area exposed by the material is adequate, and it is possible to prevent the lithium ion transmission path in the solid from being too long due to the particles being too large, and to prevent the deterioration of the surface structure from being accelerated due to the particles being too small.

[0042] 6) In the ternary cathode material of the present invention, the sintering method used includes normal mixing and sintering processes, but it is important to note that in the secondary sintering, the Mn-containing compound and the Co-containing compound must be added in advance and mixed uniformly. The ratio of the two must be 1:4 to 1:1. Otherwise, the Li-Co-Mn-O compound having a layered structure cannot be formed on the surface of the single crystal material, and the effect of the present invention, that is, the enhancement of the thermal stability of the material without obviously adversely affecting the capacity per gram and rate characteristics of the material, may not be achieved.

[0043] 7) The positive electrode sheet and the lithium ion battery using the positive electrode material according to the present invention have high thermal stability and excellent stability in long-term cycles. Other characteristics, objects and advantages of the present invention will become apparent from the following detailed description of non-limiting embodiments, which is given with reference to the accompanying drawings, in which: [Brief description of the drawings]

[0044] [Figure 1] FIG. 1 is a SEM image of the single crystal high nickel positive electrode material according to Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0045] The present invention will be described in detail below with reference to the examples. The following examples are provided to help those skilled in the art to better understand the present invention, and are not intended to limit the present invention. It should be noted that those skilled in the art may make some adjustments or improvements without departing from the spirit of the present invention. All of these are within the scope of protection of the present invention.

[0046] Example 1 This example relates to a ternary cathode material for lithium-ion batteries, the chemical composition of which is theoretically Li 1.02 Ni 0.805 Co 0.127 Mn 0.068 The fabrication process is as follows:

[0047] 1) Preparation of ternary positive electrode precursor containing Ni, Co, and Mn First, a 2 mol / L solution was prepared from three metal salts consisting of nickel sulfate, cobalt sulfate, and manganese sulfate in a molar ratio of 83:11:6. Using a peristaltic pump, a mixed solution of sodium hydroxide (4 mol / L) and ammonia water (2.4 mol / L) as a precipitant was slowly pumped into the reaction tank containing the above metal salt solution in a volume ratio of 1:1. The reaction temperature was strictly maintained at 55°C ± 1°C, the pH value of the reaction was 11.0, the stirring speed was 1000 r / min, and nitrogen gas was introduced as a protective gas during the reaction process. After reacting for 12 h, the material obtained by the reaction was washed several times with deionized water and vacuum dried at 80°C for 24 h to obtain a ternary hydroxide precursor.

[0048] 2) A ternary positive electrode precursor containing Ni, Co, and Mn was thoroughly mixed with lithium hydroxide to provide a lithium hydroxide:precursor molar ratio of 1.05:1 to form Mixture A.

[0049] 3) Mixture A was heated in an oxygen gas atmosphere and held at 910°C for 9 hours, and intermediate product B was obtained through roller and pulverization.

[0050] 4) Intermediate product B was thoroughly mixed with MnO(OH) and Co(OH)2 to form mixture C. The molar ratio of MnO(OH) to intermediate product B was 0.7%, the molar ratio of Co(OH)2 to intermediate product B was 2.1%, and the molar ratio of the two was 1:3.

[0051] 5) Mixture C was heated in an oxygen gas atmosphere, held at 820° C. for 5 hours, and then subjected to rolling and pulverization to obtain the ternary positive electrode material for lithium ion batteries.

[0052] All of the following examples and comparative examples follow similar steps, with the differences being the selection of the precursor ratios, the selection of temperature / time during steps 3) and 5), etc., all of which are shown in Tables 1 and 2.

[0053] Example 2 The preparation process of the material was almost the same as that of Example 1, except that the proportions of MnO(OH) and Co(OH)2 in step 4) were adjusted to 1.0% and 2.0%. The theoretical chemical composition of the final material was Li 1.02 Ni 0.806 Co 0.123 Mn 0.071 The SEM image of the single crystal high nickel positive electrode material thus fabricated is shown in Figure 1.

[0054] Example 3 The preparation process of the material was almost the same as that of Example 1, except that the proportions of MnO(OH) and Co(OH)2 in step 4) were adjusted to 3.5% and 4.0%. The theoretical chemical composition of the final material was Li 1.03 Ni 0.764 Co 0.135 Mn 0.101 It was O2.

[0055] Example 4 The material preparation process was almost the same as in Example 1, except that the molar ratio of the three metal salts consisting of nickel sulfate, manganese sulfate, and cobalt sulfate in step 1) was adjusted to 90:5:5, the heating temperature in step 3) was adjusted to 890°C, MnO(OH) in step 4) was adjusted to MnO2, Co(OH)2 in step 4) was adjusted to CoOOH, the mass ratio of MnO2 to intermediate product B was set to 1.5%, the mass ratio of CoOOH to intermediate product B was set to 2.5%, and the heating temperature in step 5) was adjusted to 800°C. The theoretical chemical composition of the finally obtained material was Li 1.03 Ni 0.856 Co 0.076 Mn 0.068 It was O2.

[0056] Example 5 The preparation process of the material was almost the same as in Example 4, except that the proportions of MnO2 and CoOOH in step 4) were adjusted to 3.0% and 3.5%. The theoretical chemical composition of the final material was Li 1.02 Ni 0.833 Co 0.084 Mn 0.083 It was O2.

[0057] Example 6 In step 2), the preparation process of the material was almost the same as in Example 5, except that ZrO2 was added as a dopant during the operation so that the molar ratio of ZrO2:precursor was 0.2%. The theoretical chemical composition of the final material was Li 1.02 Ni 0.830 Co 0.087 Mn 0.081 Zr 0.002 O2, i.e. Li 1.02 (Ni 0.832 Co 0.087 Mn 0.081 ) 0.998 Zr 0.002 It was O2.

[0058] Comparative Example 1 The preparation process of the material was almost the same as in Example 1, except that MnO(OH) and Co(OH)2 were not added in step 4). The theoretical chemical composition of the final material was Li 1.04 Ni 0.830 Co 0.108 Mn 0.062 It was O2.

[0059] Comparative Example 2 The preparation process of the material was almost the same as that of Example 1, except that the proportions of MnO(OH) and Co(OH)2 in step 4) were adjusted to 0.4% and 2.4%. The theoretical chemical composition of the final material was Li 1.02 Ni 0.801 Co 0.132 Mn 0.067 It's O2.

[0060] (Comparative Example 3) The material preparation process was almost the same as that of Example 1, except that the proportions of MnO(OH) and Co(OH)2 in step 4) were adjusted to 1.0% and 0.7%. The theoretical chemical composition of the final material was Li 1.03 Ni 0.813 Co 0.114 Mn 0.073 It's O2.

[0061] Comparative Example 4 The preparation process of the material was almost the same as that of Example 2, except that MnO(OH) was changed to MnSO4 and Co(OH)2 was changed to CoSO4 in step 4). The theoretical chemical composition of the final material was Li 1.02 Ni 0.800 Co 0.125 Mn 0.075 It's O2.

[0062] [Material identification] Particle size measurement: The sample was dispersed in water and placed in a laser particle sizer for measurement. The particle diffraction coefficient was set to 1.741, the absorption coefficient to 1, and the solvent diffraction coefficient to 1.330. During the measurement, the internal ultrasonic of the measuring instrument was turned on, and the light blocking degree was set to 10% to 20%. The volume distribution differential curve was selected, and the D was calculated by the software. v50 It was read as follows.

[0063] ICP measurement: 0.4g of the cathode material sample was weighed into a 250ml beaker, 10ml of HCl solution (HCl:H2O volume ratio 1:1) was added, and then it was heated to 180℃ to dissolve. After heating, the liquid was transferred to a measuring flask and made to volume with pure water, then diluted to a measurable range and measured with an ICP device. The x and y values ​​of Ni, Co, and Mn elements were calculated by comparing the relative contents according to the ICP measurement results, and a, b, and c were obtained directly by ICP measurement. When M and A are more than one type, b and c are the sum of the contents of different elements.

[0064] XPS measurement: The powder sample of the cathode material was spread on an aluminum foil with double-sided tape, the sample was pressed with a press, and the material was measured with an XPS instrument. In the measurement process, a survey scan was first performed to identify the possible element types present, and then a narrow scan was performed for the elements present. The relative atomic content of the elements was calculated based on the signal peak area and the relative sensitivity coefficient of the elements.

[0065] In the examples and comparative examples, the above particle size, ICP, and XPS measurements were performed on the ternary positive electrode materials after the grinding in step (5). The results are summarized in Table 2.

[0066] [Table 1]

[0067] In Comparative Example 1, no surface treatment was performed, so C Mn -(1-xy) ≧ 0.07 is not satisfied, and C Co -y ≧ 0.05 is not satisfied and 0 ≦ [C Mn -(1-xy)] / (C Co In Comparative Example 2, the amount of Mn coating material was too small, and C Mn The requirement of -(1-xy)≧0.07 is not met, and the requirement of 1:4-1:1 is not met during the process. In Comparative Example 3, the amount of Co coating is too small, and the C Co -y≧0.05 is not satisfied and [C Mn -(1-xy)] / (C Co -y)≦2.0 is not satisfied, and the requirement of 1:4-1:1 is not satisfied during the process. In Comparative Example 4, MnSO4 is used, which is difficult to form a layer structure, and a large amount of it remains on the surface, and [C Mn -(1-xy)] / (C Co -y)≦2.0 is not satisfied.

[0068] [Table 2]

[0069] As can be seen from the comparison between Examples 1-3 and Examples 4-5, with the increase in the amount of coating agent used, both Co and Mn increase on the surface of the material. As can be seen from the investigation of Example 2 and Comparative Example 4, if a suitable coating agent is not used, a coating layer with Li-Co-Mn-O layered structure cannot be formed under the same conditions, and Mn element may accumulate on the surface.

[0070] [Performance measurement] Batteries were produced from the ternary positive electrode materials of the examples and comparative examples by the following method, and their performance was measured.

[0071] The positive electrode active material (the prepared ternary positive electrode material), carbon black as a conductive agent, and polyvinylidene fluoride (PVDF) as an adhesive were mixed in a mass ratio of 97:1.7:1.3, and the mixture was added to N-methylpyrrolidone (NMP) as an organic solvent and stirred at high speed to form a uniform dispersion. After high speed stirring, the mixture was defoamed under negative pressure in a stirring tank to obtain a positive electrode slurry suitable for coating. The obtained positive electrode slurry was applied onto aluminum foil using a transfer coater, and after drying, cold rolling, and division, a positive electrode sheet of a specified shape was produced. During the cold rolling process, the compression density of the positive electrode active material application area was reduced to 3.4 g / cm. 3 I did.

[0072] The negative electrode active material graphite, the conductive agent carbon black, the adhesives styrene butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC-Na) were mixed in a mass ratio of 96.8:1.2:1.2:0.8, added to deionized water and stirred at high speed to form a uniform dispersion. After high speed stirring, the mixture was defoamed under negative pressure in a stirring tank to obtain a negative electrode slurry suitable for application. The obtained negative electrode slurry was applied to copper foil using a transfer coater, and after drying, cold rolling and division, a negative electrode sheet of a specified shape was produced. During the cold rolling process, the compression density of the negative electrode active material application area was reduced to 1.65 g / cm. 3 I did.

[0073] The positive and negative electrode sheets were placed on both sides of a 9 μm thick PE separator and rolled to form a roll core, and the uncoated areas and nickel tabs were connected by ultrasonic welding. The roll core was covered with aluminum-plastic film, heat sealed, and set aside for injection.

[0074] 13wt% (calculated based on the total mass of the electrolyte) LiPF6, 1wt% (calculated based on the total mass of the electrolyte) vinylene carbonate, and 2wt% (calculated based on the total mass of the electrolyte) DTD were added as lithium salt and dopant to a mixed solvent with a mass ratio of EC:EMC:DEC of 3:5:2, to prepare an electrolyte, which was then injected into an aluminum-plastic film covering a roll core. The resulting solution was then vacuum sealed, left to stand, and subjected to a chemical conversion process to obtain a lithium-ion battery.

[0075] Rate measurement: Using a charging / discharging device, the battery's SOC was adjusted to 0% at a rate of 0.33C (i.e., the current magnitude was 0.33 times the battery's rated capacity ampere-hours), and after leaving it for 30 minutes, the battery was charged at a constant current of 0.5C A at 25°C, and the capacity C1 during the charging process was recorded. Discharging at 0.33C to 0% SOC was repeated, and after leaving it for 30 minutes, the battery was charged at a constant current of 2C A, and the capacity C2 during the discharging process was recorded. C2 / C1 was used as a comparative index of rate characteristics.

[0076] Thermal stability measurement: Using a charge-discharge device, the battery's SOC was adjusted to 100% at a rate of 0.33C, the battery was disassembled in a glove box, and the positive electrode sheet was removed. A sample of about 2mm x 2mm was taken from the coating area of ​​the electrode sheet, its weight m1 was measured in air, and it was placed in a high-pressure crucible. 1 / 4ml of electrolyte was measured and dropped into the high-pressure crucible with a pipette, sealed, and measured on a DSC device at a heating rate of 5℃ / min. The apex of the peak in the curve was taken, and that temperature was used as a comparative index of thermal stability.

[0077] Measurement of high-temperature gas generation: Using a charge / discharge device, the battery's SOC was adjusted to 100% at a rate of 0.33C, and the battery volume V1 was recorded. The battery was then stored in an oven maintained at a temperature of 70 degrees, and the battery volume V2 after 72 hours was recorded. The volume increase rate due to gas generation, V2 / V1-1, was used as a comparative index of high-temperature gas generation.

[0078] Cycle life: Using charge / discharge equipment, the battery was cycled at a rate of 1C at 45°C, and the capacity retention rate after 1,000 cycles was recorded and used as a comparative index for cycle life.

[0079] The performance measurement results are shown in Table 3.

[0080] [Table 3]

[0081] As can be seen by comparing Examples 1-3 and Comparative Example 1, if the material is co-coated with Co / Mn within the preferred range of the present invention, the thermal stability and cycle stability of the material can be effectively improved while maintaining the rate characteristics of the material, and the amount of gas generated by the material in a high-temperature storage environment can be reduced. As can be seen from Examples 4-5, this tendency also applies to precursors with Ni content of 90% or more. As can be seen from Examples 5 and 6, the addition of doping element Zr in step S1 does not affect the effect of the subsequent co-coating process, and both effects can be simultaneously exerted. In Comparative Example 2, the amount of coating agent added in the coating process is close to that of Example 1, but the amount of Mn-containing coating agent added is too small to effectively improve the surface stability of the material. In Comparative Example 3, the ratio of the coating agent containing Mn and Co elements added in the coating process is inappropriate, and the difference between the content of Mn and Co elements on the surface of the material and the overall content does not meet the preferred conditions of the present invention, so that the Li-Co-Mn-O layered structure coating layer is difficult to form on the surface of the material, and the effect is difficult to be exerted. The Mn-containing coating used in Comparative Example 4 cannot react with the Co-containing coating and the residual lithium salt on the surface, and the Li-Co-Mn-O layer structure is not formed. Although the Mn and Co elements are similarly collected on the surface of the material, the high temperature stability of the material cannot be improved, and the rate characteristic of the material is deteriorated.

[0082] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above-mentioned specific embodiments, and that those skilled in the art can make various modifications or alterations within the scope of the claims without affecting the substance of the present invention.

Claims

1. Chemical composition is Li a (Ni x Co y Mn 1-x-y ) 1-b M b O 2-c A c and 0.75≦a≦1.2, 0.75≦x<1, 0<y≦0.15, 1−x−y>0, 0≦b≦0.01, and 0≦c≦0.2, M is selected from one or more of Al, Zr, Ti, Y, Sr, W, and Mg; A is a ternary positive electrode material for a lithium ion battery selected from one or more of S, F, and N, The ternary cathode material has a single crystal morphology, and C Mn −(1−x−y)≧0.07, and C Mn is the atomic ratio of Mn element to the total of Ni, Co, and Mn elements obtained by surface measurement of the material by XPS, C Co -y≧0.05, and C Co is the atomic ratio of Co to the total of Ni, Co, and Mn elements obtained by surface measurement of the material by XPS, 0≦[C Mn -(1-x-y)] / (C Co -y)≦2.0; Ternary positive electrode material for lithium-ion batteries.

2. C Mn The ternary positive electrode material for lithium ion batteries according to claim 1, wherein -(1-x-y)≧0.

15.

3. C Co The ternary positive electrode material for lithium ion batteries according to claim 1, wherein -y≧0.

1.

4. The particle size D when the particle volume cumulative distribution of the ternary positive electrode material reaches 50% v50 However, 2.5 μm≦D v50 The ternary positive electrode material for lithium ion batteries according to claim 1, wherein the average particle size is less than or equal to 5 μm.

5. A method for producing the ternary positive electrode material for a lithium ion battery according to claim 1, comprising the steps of: S1: Select a ternary positive electrode precursor containing Ni, Co, and Mn, and mix it with lithium hydroxide to form mixture A; S2: Heat the mixture A in an air or oxygen gas atmosphere, hold it at 700°C to 1100°C for 4 hours to 15 hours, and then pass it through a roller and grind to obtain an intermediate product B; S3: mixing intermediate product B with Mn-containing solid powder and Co-containing solid powder to form mixture C, in which the ratio of the substance amount of Mn element in the Mn-containing solid powder to the substance amount of intermediate product B is 0.5% to 4%, and the ratio of the substance amount of Co element in the Co-containing solid powder to the substance amount of intermediate product B is 2% to 4%; S4: Mixture C is heated in an air or oxygen gas atmosphere, and held at 700° C. to 1100° C. for 4 to 15 hours, and then subjected to rolling and pulverization to obtain the ternary positive electrode material for lithium ion batteries.

6. In step S1, an oxide of element M is added as a dopant; and / or In step S3, an oxide of element M is added as a coating agent; and / or In step S1, a compound containing element A is added as a dopant; and / or In step S3, a compound containing element A is added as a coating agent. A method for producing the ternary positive electrode material for a lithium ion battery according to claim 5.

7. In step S3, the Mn-containing solid powder is treated to obtain MnO 2 , Mn 2 O 3 , MnO(OH), MnO, Co-containing solid powder 3 O 4 , CoO, Co(OH) 2 , CoOOH, CoCO 3 The method for producing a ternary positive electrode material for a lithium ion battery according to claim 5, wherein the ternary positive electrode material is selected from any one or more of the following:

8. 6. The method for producing a ternary positive electrode material for a lithium ion battery according to claim 5, wherein in step S3, a ratio of amounts of Mn element to Co element in the Mn-containing solid powder and the Co-containing solid powder is 1:4 to 1:

1.

9. A positive electrode sheet for a lithium ion battery comprising the ternary positive electrode material according to any one of claims 1 to 4.

10. A lithium ion battery comprising the positive electrode sheet according to claim 9.

Citation Information

Patent Citations

  • Positive electrode active material for a lithium secondary battery having a total particle concentration gradient, a method for producing the same, and a lithium secondary battery containing the same.

    JP2014506388A

  • Positive electrode active material for secondary battery, method for producing the same, and secondary battery including the same

    JP2018515884A

  • Surface-stabilized cathode materials for lithium-ion batteries and methods for synthesizing same

    JP2019530630A

  • Positive electrode active material, its manufacturing method, and lithium secondary battery including the same

    JP2020514972A

  • Positive electrode active material for secondary battery, method for producing the same, and lithium secondary battery including the same

    JP2020537315A